2012
DOI: 10.4081/reumatismo.2012.261
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia and sexual problems

Abstract: The aim of this review was to describe the recent literature concerning sexual dysfunction in fibromyalgic patients. To this end, we used the common online databases PubMed, MEDLINE and EMBASE (up to June 2012) and searched for the key words fibromyalgia (FM) and sexual dysfunction. All the studies examined underlined that FM is strictly associated with sexual dysfunction in women. The major findings observed were related to a decreased sexual desire and arousal, decreased experience of orgasm, and in some stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
4
24
0
2
Order By: Relevance
“…Women with fibromyalgia report sexual dysfunction primarily related to diminished desire, low arousal and decreased orgasm. [17] Various dermatologic conditions, such as Behcet’s disease and psoriasis, also impact sexual functioning. [1820] A large proportion of our participants (80%) had chronic vulvovaginitis symptoms that had been present for over a year, which could suggest that their dysfunction relates to having chronic medical illness rather than symptoms intrinsic to vulvovaginitis.…”
Section: Discussionmentioning
confidence: 99%
“…Women with fibromyalgia report sexual dysfunction primarily related to diminished desire, low arousal and decreased orgasm. [17] Various dermatologic conditions, such as Behcet’s disease and psoriasis, also impact sexual functioning. [1820] A large proportion of our participants (80%) had chronic vulvovaginitis symptoms that had been present for over a year, which could suggest that their dysfunction relates to having chronic medical illness rather than symptoms intrinsic to vulvovaginitis.…”
Section: Discussionmentioning
confidence: 99%
“…The higher presence of arousal problems in patients suffering from FM and/or other chronic pain conditions has been previously reported by a number of studies (e.g., Refs. 21, 42, and 43). The major factor affecting these women's sexual response is not only the constant pain presence but also related psychological aspects (such as symptoms of depression, stress) and CWP‐related somatic symptoms such as fatigue and sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature have found a close correlation between FMS and sexual dysfunction. The main symptoms include decreased sexual drive, excitement, orgasm, and increased genital pain ( 2 ) . From a psychological point of view, stress, chronic generalized pain, fatigue, and sleep disorder negatively affect the sexual life of patients with FMS.…”
Section: Introductionmentioning
confidence: 99%